Preparation and Characterization of Some Hyperbranched Polyesteramides/Montmorillonite Nanocomposites - Amal Amin; Moshera Samy (International Journal of Polymer Science)
Different polyesteramides hyperbranched polymers (HPEA1-6)/montomorillonite clay (MMT) nanocomposites were prepared with three different loading contents of clay (4, 10, and 15 wt%). The obtained nanocomposites were characterized via XRD, thermal analyses, and TEM. Generally, intercalation behavior was observed. The hyperbranched polyesteramides (HPEA1-6) were originally prepared by the bulky reaction between maleic anhydride (MAn), succinic anhydride (ScAn), and phthalic anhydride (PhAn) with either diethanolamine (DEA) or diisopropanolamine (DiPA). The resulting hyperbranched polyesteramides (HPEA1-6) were characterized by GPC, IR, 1H-NMR, TGA, and DSC.